Shunt hybrid active power filter based on two compensation strategies with PI and fuzzy logic controllers - Omran, Mohamed Asghaiyer; Izzeldin, I. Mohd; Almelian, Mohamad Milood; Dawood, Mohammed A.; Al-Izzi, M. Y. (UTeM, 2018)
Industrial designs have tremendously changed within the last decade, with its time and nonlinear variation loads in power frameworks spectrum expanding widely. This revolution has resulted in increased quality control problems such as current unbalance, current and voltage harmonics, flicker and poor power factor in control frameworks. The aim of this paper is to address this problem through the development of Synchronous Reference Frame and Reactive Power (SRF and P-Q) control methods. The DC voltage was regulated to its set reference for providing the current reference using proportional-Integral (PI) and fuzzy logic controllers. From the results, Fuzzy logic control was shown to achieve an adequate DC capacitor energy storage optimization, the sinusoidal type of the current and the change of the power factor. A low Total Harmonic Distortion (THD) that met the suggestions of IEEE- 519 standard on symphonious levels was achieved with the proposed method.